Aplastic anemia in rural Thailand: Its association with grain farming and agricultural pesticide exposure - Surapol Issaragrisil (2018)
Objectives. A population-based case-control study was conducted to elucidate the incidence and etiology o aplastic anemia in Thailand. Methods. Case patients and hospital control patients were enrolled in three regions from 1989 to 1994; data were collected by interview. Results. Forty-six percent of 81 case patients and 19% of 295 control patients from Khonkaen were grain farmers (estimated relative risk [RR] = 2.7, 95% confidence interval [CI] = 1.4, 5.2). Sixteen percent of case patients and 6% of control patients used agricultural pesticides (estimated RR= 2.7, 95% CI= 1.1, 6.6). The association with grain farming remained among those not exposed to pesticides. In Songkla, 16% of 43 case patients and 2% of 181 control patients were grain farmers (crude RR estimate = 11, 95% CI = 3.4, 35). Conclusions. The relation of aplastic anemia to grain farming may partly explain the high incidence of aplastic anemia in Thailand.